2009
DOI: 10.1292/jvms.71.831
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi-Like Vascular Tumor of the Urinary Bladder in a Cow

Abstract: ABSTRACT. Kaposiform hemangioendothelioma is a rare human vascular neoplasm. In veterinary medicine this tumor type was only recognized in the dog. Here we describe an unusual case arising in the urinary bladder of a Holstein-Friesian adult cow. Histologically the tumor presented a nodular proliferation of spindle cells, forming angular slits, often containing extravasated erythrocytes. Peripherically, well-formed vascular channels were seen. These cells were positive to vimentin and to factor VIII-related ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…They were classified as Kaposi-like hemangioendotheliomas since they were characterized by a proliferation of fusiform tumor cells with eosinophilic cytoplasm and elongated nuclei, showing moderate atypia, associated to features of capillary hemangioma (Figure 2(e)). Kaposi-like hemangioendothelioma is extremely rare, and it has recently been described in the urinary bladder in a cow [36]. …”
Section: Resultsmentioning
confidence: 99%
“…They were classified as Kaposi-like hemangioendotheliomas since they were characterized by a proliferation of fusiform tumor cells with eosinophilic cytoplasm and elongated nuclei, showing moderate atypia, associated to features of capillary hemangioma (Figure 2(e)). Kaposi-like hemangioendothelioma is extremely rare, and it has recently been described in the urinary bladder in a cow [36]. …”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed that under weak alkaline conditions, dienone 2 exhibits significant alkylating activity, leading to the cleavage of deoxyribonucleic acid (DNA). Consumption of bracken fern in high doses can cause DNA damage, resulting in programmed cell death and cell cycle arrest even at lower doses [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…27 Human Kaposi's sarcoma is believed to be derived from capillary endothelial cells. 41 In contrast, cytologic features of the tumors in the present study are consistent with origin from 2 types (smooth muscle and endothelial) of cell and, thus, are distinct from Kaposi's sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization Histological Classification of Tumors of Domestic Animals includes the Kaposi-like vascular tumor, 12 which has been reported in a dog 30 and a cow. 27 Human Kaposi’s sarcoma is believed to be derived from capillary endothelial cells. 41 In contrast, cytologic features of the tumors in the present study are consistent with origin from 2 types (smooth muscle and endothelial) of cell and, thus, are distinct from Kaposi’s sarcoma.…”
Section: Discussionmentioning
confidence: 99%